2022
DOI: 10.3390/vetsci9040167
|View full text |Cite
|
Sign up to set email alerts
|

Cross Species Analysis and Comparison of Tumors in Dogs and Cats, by Age, Sex, Topography and Main Morphologies. Data from Vet-OncoNet

Abstract: The animal cancer burden is essential for the translational value of companion animals in comparative oncology. The present work aims to describe, analyze, and compare frequencies and associations of tumors in dogs and cats based on the Animal Cancer Registry created by Vet-OncoNet. With 9079 registries, regarding 2019 and 2020, 81% (n = 7355) belonged to dogs. In comparison, cats have a general one-year right advance in the mean age of cancer diagnosis compared to dogs. The multivariate topography group analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 44 publications
6
29
2
1
Order By: Relevance
“…Findings from this study showed that neoplasms were more common in male dogs (57.1%) than in female dogs (42.9%) whereas in cats, it was more common in females (66.7%) than in males (33.3%). Several studies on the prevalence of neoplasms in dogs and cats reported a higher prevalence in females than males and attributed it to the preponderance of mammary gland tumors in females [3,6,13,14,15]. However, no case of mammary gland tumor was recorded in female dogs in this study, which could probably be the reason why the prevalence of neoplasms was higher in male dogs.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Findings from this study showed that neoplasms were more common in male dogs (57.1%) than in female dogs (42.9%) whereas in cats, it was more common in females (66.7%) than in males (33.3%). Several studies on the prevalence of neoplasms in dogs and cats reported a higher prevalence in females than males and attributed it to the preponderance of mammary gland tumors in females [3,6,13,14,15]. However, no case of mammary gland tumor was recorded in female dogs in this study, which could probably be the reason why the prevalence of neoplasms was higher in male dogs.…”
Section: Discussioncontrasting
confidence: 55%
“…This suggests that dogs may be more susceptible to neoplasms than cats. A higher prevalence of neoplasms in dogs compared to cats is commonly reported [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipomas present in the database were removed from this study. The topographies were grouped into 14 systems, as per our previous study [ 24 ]. The tumors on “Soft Tissue” represent tumors occurring in the connective, subcutaneous, and other soft tissues, when this information was available, according to Vet-ICD-O.…”
Section: Methodsmentioning
confidence: 99%
“…Skin cancers are also among the most commonly diagnosed diseases in animals. The canine species has been identified as the species with the highest prevalence of skin malignancies, accounting for one-third of all tumors diagnosed in it [ 4 ]. In the case of cats, skin cancers play a crucial role, accounting for one-quarter of all neoplasias diagnosed in this species.…”
Section: Introductionmentioning
confidence: 99%